Review of research on salt-affected soils in the Debrecen agricultural high educational institutions, with special focus on the mapping of Hortobágy - Tóth, Tibor; Pásztor, László; Árvai, Mátyás; Sipos, György; Takács, Katalin; Rékasi, Márk; Szatmári, Gábor; Balog, Kitti; Kovács, Zsófia Adrienn (Acta Agraria Debreceniensis, 2018)
The history of the research of Debrecen scholars on salt-affected soils of Hortobágy and the region is very rich and diverse. Focusing on mapping, the following stages can be distinguished, indicating the completeness of the maps and the purpose of the performed work − First, quantitative maps (Arany, 1926) for the utilization of the lands at 1:75,000 (Figure 1). − Second, quantitative map (Kreybig, 1943) for the utilization of the lands at 1:25,000. − Third, category map (Kreybig et al., 1935) testing the suitability of the classification system at :75,000. − Fourth, partial category map (Szabolcs, 1954), showing the reasons of unsuccessful management at 1:10,000. − Fifth, partial quantitative map (Csillag et al., 1996), showing the utility of digital sampling at 1:25,000. − Sixth, partial quantitative map (Tamás and Lénárt, 2006), showing the capacity of multispectral remote imagery at 1:100. − Seventh, partial quantitative map (Douaik et al., 2006), showing the usefulness of geostatistical mapping at 1:10,000. − Eight, national quantitative maps (Pásztor et al., 2016), showing the applicability of geostatistics for administrative purposes at 1:10,000. − Ninth, partial quantitative/category map (authors, 2019), finding the optimal methods at 1:10,000.